A Survey of Migrant Women’s Experiences’ Studies from a Gender Perspective - Ramingwong, Palinda (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
This paper aims to explore the studies of the gender concepts of women migrants in low-wage jobs and their adaptation strategies through a review of relevant secondary documents. Although women make up more than half of the world’s migrants, early academic studies on migration ignored the experiences of women and viewed their experiences as no different from that of male migrant workers. This has resulted in issues of discrimination and restriction of access to welfare for women workers. When protested by feminist scholars, academic works on migrant women have been increasingly produced since the 1980s and could point to the unique characteristics or experiences of female migrant workers as a result of the gender structure that constitutes a patriarchal society. The study also seeks to explore the countermeasure and negotiating strategies for the obstacles they put in place for the survival of themselves and their families, which vary in age, ethnicity, culture, education, income, occupation, network, resources, and capital. That is, they use different types of capital, including economic capital, social capital, and cultural capital to adapt and negotiate to the situations they face in destination countries. Understanding the experiences of migrant women will lead to the creation of appropriate policies and gender equality in accordance with Goal 5 of the Sustainable Development Goals in both the countries of origin and destination.